Determinasi Terhadap Kualitas Informasi Finansial Pemerintah Daerah - Purba, Sahala (EQUITY, 2022)
The problem with the quality of local government financial information is the irrelevantness of the financial information presented in accordance with applicable ethics. Local government financial information can be problematic due to low human resources with accounting knowledge in the preparation of financial information, weak government internal management systems, not optimal use of information technology and less than optimal internal audit function in carrying out its functions effectively and efficiently. The purpose of this study is to understand and analyze the impact of accounting knowledge, the government's internal management system, the use of information technology and the internal audit function partially or simultaneously. This form of observation describes causal associative observations and uses primary data. The data collection system used is a questionnaire. descriptive analysis and multiple linear regression. form of analysis used in this observation. This research was conducted in Regional Apparatus Organizations throughout Deli Serdang Regency. Respondents in this study were 69 people. The results of this study prove that partially accounting knowledge, government internal management systems and the use of information technology have a positive effect on the quality of local government financial reports, while the internal audit function has a negative effect on the quality of local government financial information. Taken together, accounting knowledge, government internal management systems and the use of information technology affect the quality of local government financial information in Deli Serdang Regency. The implications of this research are that good accounting knowledge is supported by a strong government internal management system, and the use of information technology and an optimal internal audit function will be able to increase the quality of local government financial information in all local governments in Indonesia, especially in the District. Deli Serdang.